A cohesive zone framework for environmentally assisted fatigue. (November 2017) - del Busto, Susana; Betegón, Covadonga; Martínez-Pañeda, Emilio
Highlights: A novel finite element framework for hydrogen-assisted fatigue is presented. The model builds upon a coupled mechanical-diffusion response and a hydrogen- and cycle-dependent cohesive zone formulation. The numerical implementation in the commercial FE package ABAQUS is appropriately described. Hydrogen transport and subsequent cracking under cyclic loading conditions are investigated. The sensitivity of fatigue crack growth rates to the loading frequency is thoroughly examined. Abstract: We present a compelling finite element framework to model hydrogen assisted fatigue by means of a hydrogen- and cycle-dependent cohesive zone formulation. The model builds upon: (i) appropriate environmental boundary conditions, (ii) a coupled mechanical and hydrogen diffusion response, driven by chemical potential gradients, (iii) a mechanical behavior characterized by finite deformation J2 plasticity, (iv) a phenomenological trapping model, (v) an irreversible cohesive zone formulation for fatigue, grounded on continuum damage mechanics, and (vi) a traction-separation law dependent on hydrogen coverage calculated from first principles. The computations show that the present scheme appropriately captures the main experimental trends; namely, the sensitivity of fatigue crack growth rates to the loading frequency and the environment. The role of yield strength, work hardening, and constraint conditions in enhancing crack growth rates as a function of the frequency is thoroughly investigated. The results reveal the need to incorporate additional sources of stress elevation, such as gradient-enhanced dislocation hardening, to attain a quantitative agreement with the experiments.